Drivers of soil respiration and nitrogen mineralization change after litter management at a subtropical Chinese sweetgum tree plantation. (30th June 2022) - He, Yiting; Wang, Yong; Jiang, Yi; Yin, Guoping; Cao, Shunping; Liu, Xiongsheng; Wang, Renjie; Wu, Zijian; Chen, Fengfan
Abstract: Leaf litter decomposition transfers elements from litter to soils that are essential for regulating nutrient cycles in plantation ecosystems, especially carbon and nitrogen. However, soil carbon and nitrogen dynamics in response to tree litter management remains insufficiently researched. We conducted a one‐year field experiment at a fast‐growing sweetgum tree plantation to evaluate the effects of leaf litter management on soil available nutrients, respiration rate and nitrogen mineralization rate. Three leaf litter treatments were applied, which were: (1) natural input (control); (2) double input and (3) non‐input. It was found that the double input treatment increased soil inorganic nitrogen and microbial biomass nitrogen, but had little effect on microbial biomass carbon, dissolved organic carbon or dissolved organic nitrogen compared with natural input. The non‐input treatment caused dissolved organic carbon to decrease compared with natural input. The respiration rate increased in the double input treatment, with a positive priming effect observed. Soil net ammonification, nitrification and mineralization rates also increased in the double input treatment in specific seasons. Meanwhile, positive linear relationships between respiration rate and all nitrogen transformation rates were observed for all treatments. Soil temperature was found to be an important prediction factor for predicting the respiration rate and mineralization as seasonal variations, but not for litter‐induced fluctuations. Soil water content and mineral nitrogen were the primary drivers of litter‐induced change to the respiration rate, whereas mineral nitrogen and microbial biomass were primary drivers of mineralization change. These results suggest that changes in soil nitrogen mineralization rate are strongly associated with the soil respiratory process, resulting in a potentially strong plant–soil feedback mechanism.